2021
DOI: 10.1177/14773708211053135
|View full text |Cite
|
Sign up to set email alerts
|

Women trafficking networks: Structure and stages of women trafficking in five Dutch small-scale networks

Abstract: In this study, we investigated the relation between the different stages of women trafficking (i.e. recruitment, entrance, accommodation, labor, and finance) and the structure of five criminal networks involved in women trafficking in the Netherlands ( Ns ranging from 6 to 15). On the one hand, it could be argued that for efficiency and avoidance of being detected by law enforcement agencies, the network structure might align with the different stages, resulting in a cell-structured network with collaboration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The final group of SNA studies examined the structure of sex trafficking networks, using records from law enforcement investigations and court cases. Generally, these studies confirmed the central role of "madams" (i.e., women formerly enslaved as prostitutes who participate in trafficking other women) and others involved in the management and control of the trafficking process, while highlighting the overall decentralized nature of the networks, with most actors on the periphery and limited to only one stage in the trafficking process (e.g., recruitment, transportation) (Campana, 2016;Cockbain et al, 2011;Diviak et al, 2021;Mancuso, 2014). Collaboration and co-offending tended to occur within the same stage of trafficking (Campana, 2016) or within smaller subgroups (i.e., cliques) of the larger network (Sabon et al, 2021).…”
Section: Social Network Analysis Studies (N = 45)mentioning
confidence: 58%
“…The final group of SNA studies examined the structure of sex trafficking networks, using records from law enforcement investigations and court cases. Generally, these studies confirmed the central role of "madams" (i.e., women formerly enslaved as prostitutes who participate in trafficking other women) and others involved in the management and control of the trafficking process, while highlighting the overall decentralized nature of the networks, with most actors on the periphery and limited to only one stage in the trafficking process (e.g., recruitment, transportation) (Campana, 2016;Cockbain et al, 2011;Diviak et al, 2021;Mancuso, 2014). Collaboration and co-offending tended to occur within the same stage of trafficking (Campana, 2016) or within smaller subgroups (i.e., cliques) of the larger network (Sabon et al, 2021).…”
Section: Social Network Analysis Studies (N = 45)mentioning
confidence: 58%
“…Future studies focussed on offender networks could further improve our understanding of such trade. In addition, the use of other criminological tools such as crime script analysis to break down the stages and actors involved in the illegal trade chain could complement this work (Diviák et al, 2021). In both networks, a few locations and routes were used disproportionately for trafficking, but our knowledge of the characteristics of the locations and routes that facilitate illegal wildlife trade concentration remains limited.…”
Section: Discussionmentioning
confidence: 99%